2011
DOI: 10.1002/ps.2277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plant‐growth‐promoting rhizobacteria, acibenzolar‐S‐methyl and hymexazol for integrated control of Fusarium crown and root rot on tomato

Abstract: The results of the study indicate that, when bacilli PGPR strains were combined with pesticides, there was an increased suppression of Forl on tomato plants, and thus they may prove to be important components in FCRR integrated management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 44 publications
0
36
0
4
Order By: Relevance
“…Omar et al (2006) similarly reported FCRR reduction from a combination of Burkholderia cepacia with a reduced rate of the fungicide carbendazim in the UK. The integration of Bacillus subtillis (Companion ® ) with either the fungicide hymexazol or the resistance elicitor acibenzolar-s-methyl produced greater reductions in the FCRR disease index than any of the treatments alone (Myresiotis et al, 2012). Integration of Trichoderma harzianum with the resistance elicitor chitosan resulted in enhanced management of FCRR in a greenhouse trial in Tunisia (ElMohamedy et al, 2014).…”
Section: Biological þ Chemicalmentioning
confidence: 97%
“…Omar et al (2006) similarly reported FCRR reduction from a combination of Burkholderia cepacia with a reduced rate of the fungicide carbendazim in the UK. The integration of Bacillus subtillis (Companion ® ) with either the fungicide hymexazol or the resistance elicitor acibenzolar-s-methyl produced greater reductions in the FCRR disease index than any of the treatments alone (Myresiotis et al, 2012). Integration of Trichoderma harzianum with the resistance elicitor chitosan resulted in enhanced management of FCRR in a greenhouse trial in Tunisia (ElMohamedy et al, 2014).…”
Section: Biological þ Chemicalmentioning
confidence: 97%
“…Mukhopadhyay, (1987). Myresiotis et al (2012) reported that when bacilli PGPR strains were combined with pesticides, there was an increased suppression of F. o.f. sp.…”
Section: Disease Severitymentioning
confidence: 99%
“…lycopersici Synder and Hansen, is the most important which causes serious economic loss in all tomato growing areas of the world. The management of the disease can be done through cultural practices (Katan, 1989), use of resistant varieties Rodriguez et al, 2003), chemical measures (Zindan et al, 2000), biological control (Gnanamanikram, 2002;Myresiotis et al, 2012;Bansal et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus pumilus, a Gram-positive bacterium belonging to the B. subtilis group (8), has been widely used as a plant growth-promoting rhizobacterium to prevent plant disease caused by pathogenic bacteria and fungi (9). However, numerous B. pumilus strains have also been reported to cause several human and plant diseases (10,11).…”
mentioning
confidence: 99%